2020
DOI: 10.1002/jsfa.10607
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of limited amounts of extruded legumes plus cereal mixes in normocaloric or obesogenic diets for rats: effects on intestinal microbiota composition

Abstract: BACKGROUND: Differences in the composition of the intestinal microbiota and energetic metabolism between lean and obese populations have been described. Legume consumption has been reported to modulate intestinal microbiota composition. However, to the best of our knowledge, no information can be found in the literature on the effects of consumption of diets containing extruded legume plus cereal mixes on the intestinal microbiota composition of rats. Our purpose was to evaluate the effects on lipids profile (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 76 publications
(157 reference statements)
2
3
1
Order By: Relevance
“…This is apparently contrary to what we found previously with other legumebased diets ( Rubio, Aranda-Olmedo, Contreras, & Góngora, 2020 ), but in that previous work we did not supplement the control diet with any additional fibre sources, except cellulose which is mostly indigestible. In fact, although not strictly comparable, it is interesting to note that variability values for the control casein diet in Rubio et al (2020) were generally lower than those here reported. The animals fed the CM12 control diet had higher faecal proportions of Bacteroides spp.…”
Section: Faecal Microbiota Compositioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This is apparently contrary to what we found previously with other legumebased diets ( Rubio, Aranda-Olmedo, Contreras, & Góngora, 2020 ), but in that previous work we did not supplement the control diet with any additional fibre sources, except cellulose which is mostly indigestible. In fact, although not strictly comparable, it is interesting to note that variability values for the control casein diet in Rubio et al (2020) were generally lower than those here reported. The animals fed the CM12 control diet had higher faecal proportions of Bacteroides spp.…”
Section: Faecal Microbiota Compositioncontrasting
confidence: 95%
“…The results here reported are very much in line with previous work by our group using other legume seed meals and/or legume seed fractions ( Aranda-Olmedo, Ruiz, Peinado, & Rubio, 2017 ;Rubio et al, 2020 ), and broadly agree with the so-called enterotypes concept introduced by Arumugam in 2011, and with work in children from Europe and rural Africa (for more details see Aranda-Olmedo et al, 2017 andRubio et al, 2020 ). In general terms, as shown in Figs.…”
Section: Faecal Microbiota Compositionsupporting
confidence: 92%
“…Finally, bile acid metabolism is known to be modulated by gut microbiota, affecting the biotransformation, reabsorption, and excretion of bile acids by catalysing a range of biochemical reactions [ 61 ]. Nakatani et al [ 62 ] have recently found an elevated cecal and faecal bile acid pool in mice that had consumed mung bean protein, and those changes were linked to dramatic changes in the gut microbiome, such as such as changes in the Firmicutes/Bacteroidetes proportions (see Rubio et al [ 16 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, new highly palatable [ 14 ] extruded mixes of legumes plus cereals similar to a snack food have been produced [ 15 ]. Two of these extruded mixes have been incorporated in the current work into normocaloric or obesogenic diets for rats to evaluate the effects on lipid profile and intestinal microbiota composition [ 16 ]. Obesogenic diets are those that promote obesity by presenting high caloric contents mainly from a high proportion of carbohydrates, usually simple sugars and/or fats [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial log 10 number of copies was determined by using quantitative polymerase chain reaction (q-PCR) (iQ5 Cycler, Bio-Rad Laboratories, Alcobendas, Spain). The 16S rRNA gene-targeted primers and polymerase chain reaction (PCR) conditions used in this study were as described previously [ 14 ]. The different microbial groups quantified included Lactobacillus spp., Bifidobacterium spp., Blautia coccoides/Eubacterium rectale group, Clostridium leptum/Ruminococcus spp., Enterobacteriaceae , Escherichia/Shigella , Bacteroides/Prevotella spp., and total bacteria.…”
Section: Methodsmentioning
confidence: 99%